Biosynthesis, characterization, and antibacterial activity of gold nanoparticles - Sivaji Sathiyaraj; Gunasekaran Suriyakala; Arumugam Dhanesh Gandhi; Ranganathan Babujanarthanam; Khalid S. Almaary; Tse-Wei Chen; K. Kaviyarasu (Elsevier, 2021)
Background: In recent decades focus of research has been toward an alternative antibacterial agent because of growing bacterial resistance and side effects of antibacterial agents. In the current study, the antibacterial activity of gold nanoparticles has been evaluated on selected human pathogens. Methods: In this study, we used panchagavya (PG) to synthesize gold nanoparticles, and the resulting nanoparticles (PG-AuNPs) were characterized by several spectroscopic techniques. In addition, antibacterial activity of PG-AuNPs against Escherichia coli, Bacillus subtilis, and Klebsiella pneumoniae were studied by well diffusion method. Results: The synthesis of AuNPs was affirmed by a colour change, which was further validated by UV-vis spectra with a maximum absorption peak at 527 nm. Bandgap energy was calculated as 2.13 eV by Tauc method from the UV result. The presence of amino acids and proteins in PG was responsible for the conversion of gold ions to AuNPs, according to FTIR analysis. (111), (200), (220), and (311) crystallographic planes were observed by XRD; further crystalline nature was validated by SAED analysis. The size and zeta value were found to be 53.29 nm and -9.8 mV respectively. Spherical shaped nanoparticles and elemental structure of PG-AuNPs were confirmed by HRTEM and EDS analysis. The antibacterial activity of PG-AuNPs showed the maximum and minimum zone of inhibition against K. pneumoniae (17.12 ± 0.14 mm) and B. subtilis (11.42 ± 0.58 mm). Conclusion: Antibacterial activity of PG-AuNPs was found to be strong against gram negative bacteria and moderate against gram positive bacteria. Based on the result, it was concluded that PG-AuNPs could be used to combat antibiotic drug resistance. Besides, in vitro and in vivo toxicity studies of PG-AuNPs should be conducted.